Anaesthetists stress is induced by patient ASA grade and may impair non-technical skills during intubation - Doleman, Brett; Blackwell, J.; Karangizi, A.; Butt, W.; Bhalla, Ashish; Lund, Jonathan N.; Williams, John P. (Wiley, 2016)
Background